2020
DOI: 10.1177/2150135120918774
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Valvuloplasty Versus Balloon Dilation for Congenital Aortic Stenosis in Pediatric Patients

Abstract: Background: For children with congenital aortic stenosis (AS) who are candidates for biventricular repair, valvuloplasty can be achieved by surgical aortic valvuloplasty (SAV) or by transcatheter balloon aortic dilation (BAD). We aimed to evaluate the longer term outcomes of SAV versus BAD at our institution. Methods: We retrospectively reviewed the outcomes of 2 months to 18 years old patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Although some initially championed open valvuloplasty for patients beyond the newborn period, 6 they and others have extended the strategy to include neonates with 7 or without significant left ventricular dysfunction. 8,9 In this study, the median age at surgery was just 0.4 years, with neonates accounting for one-quarter of patients. 1 Survival for neonates was outstanding, with no hospital deaths and just 1 late noncardiac death.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Although some initially championed open valvuloplasty for patients beyond the newborn period, 6 they and others have extended the strategy to include neonates with 7 or without significant left ventricular dysfunction. 8,9 In this study, the median age at surgery was just 0.4 years, with neonates accounting for one-quarter of patients. 1 Survival for neonates was outstanding, with no hospital deaths and just 1 late noncardiac death.…”
mentioning
confidence: 71%
“…While some recommend judicious tricuspidization as needed, 10 others caution against it, especially in infants and young children. 6,8,9 It can be a difficult dilemma, and one may have to weigh the competing risks of a suboptimal result due to residual stenosis of an intact raphe versus the risk of reoperation due to patch support of the divided raphe. Still, some patch techniques may be less egregious than others.…”
mentioning
confidence: 99%
“…Brain MRI studies have revealed a pattern of delayed brain maturation and evidence of chronic diffuse white matter injury in foetuses with AVS with secondary HLHS. In addition, abnormal neurologic exams and microcephaly have also been noted in neonates with AVS with secondary HLHS [47][48][49]. A low-average to average IQ range in conjunction with mild deficits in a range of domains such as executive function and social cognition is common amongst children with wide-ranging diagnoses of CHD.…”
Section: Long-term Results and Outcomesmentioning
confidence: 99%
“…These authors suggest comparison of in-hospital days and morbidity associated with both forms of therapy in future studies. However, single institutional studies differ in their conclusions with some suggesting comparable outcomes [92][93][94] and others favoring surgery [94][95][96]. Therefore, the author favors BAV because of considerable occurrence of mortality, both early and late, universal morbidity and the necessity for reoperation seen with surgical valvotomy.…”
Section: Comparison With Surgerymentioning
confidence: 99%